Pseudotumor Cerebri in the Setting of Differentiation Syndrome in a Patient with Acute Promyelocytic Leukemia Treated with All-trans Retinoic Acid During Induction Therapy - Suwal, Barsha; Poudyal , Bishesh Sharma; Adhikary, Rabindra (Nepal Journal of Neuroscience, 2021)
Introduction: Differentiation syndrome, a well-known complication of all-trans retinoic acid (ATRA) in patients with acute promyelocytic leukemia (APML), can very rarely have ophthalmic manifestations. Pseudotumor cerebri (PC) in the setting of differentiation syndrome (DS) in patients undergoing induction with all-trans retinoic acid has rarely been reported elsewhere. We herein report one such case. Case Presentation: A 28-year-old, non-obese female diagnosed as acute promyelocytic leukemia underwent induction with all- trans retinoic acid and Idarubicin. On day 4 of the treatment, she developed high grade fever (104 – 105 F), dry cough, hypotension, tachycardia, and tinnitus. Chest X ray showed floppy shadows in bilateral lungs. On physical examination, bilateral lower limb edema was noted. She also experienced sudden weight gain of 5 kilogram in 48 hours. After careful exclusion of systemic infection, she was suspected as having DS. She also noticed a reduction in vision in right eye. On eye examination, her best-corrected visual acuity (VA) was 6/60 in the right eye (RE) and 6/6 in the left eye (LE). Fundus evaluation revealed bilateral disc edema with peripapillary hemorrhages along with slight tortuosity of vessels and a yellowish lesion over the fovea in RE. Suspecting DS, she was treated with injection dexamethasone 10 mg twice daily and all- trans retinoic acid was temporarily discontinued. Immediately after its discontinuation, her headache lessened and vision improved gradually. After 2 weeks, her VA was 6/12 in RE and 6/6 in LE which improved to 6/6 in both eyes at 3 months. The patient was also receiving oral voriconazole for fungal prophylaxis and the potentiation effect of all- trans retinoic acid could thus be explained. Conclusion: Pseudotumor cerebri associated with all-trans retinoic acid treatment in acute promyelocytic leukemia, even though frequently reported in pediatric patients, is rare in adults. Ophthalmological evaluation is mandatory in all these patients under all-trans retinoic acid therapy.